2009
DOI: 10.1021/ja8095976
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Steroidal Antibiotic Fusidanes: Functional Analysis of Oxidosqualene Cyclase and Subsequent Tailoring Enzymes from Aspergillus fumigatus

Abstract: Three putative oxidosqualene cyclase (OSC) genes exist in the genome of the fungus Aspergillus fumigatus that produces a steroidal antibiotic, helvolic acid. One of these genes, Afu4g14770, designated AfuOSC3, is clustered with genes of cytochrome P450 monooxygenases (P450s), a short-chain dehydrogenase/reductase (SDR), and acyltransferases, which presumably function in triterpene tailoring steps, suggesting that this gene cluster codes for helvolic acid biosynthesis. AfuOSC3 was PCR amplified from A. fumigatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Our genome survey indicated that the homolog of this protein is present not only in the non-specialists (e.g., MAA_03020 of M. robertsii , 82% identity) but also in M. acridum (MAC_02619, 80%) and M. album (MAM_05601, 75%). A previous study in Aspergillus fumigatus indicated that an oxidosqualene cyclase (Afu4g14770) is required for helvolic acid biosynthesis (Mitsuguchi et al, 2009). Likewise, the homolog of this cyclase is present in M. robertsii (MAA_06578, 63%), M. acridum (MAC_09947, 38%), and M. album (MAM_07210, 39%).…”
Section: Discussionmentioning
confidence: 99%
“…Our genome survey indicated that the homolog of this protein is present not only in the non-specialists (e.g., MAA_03020 of M. robertsii , 82% identity) but also in M. acridum (MAC_02619, 80%) and M. album (MAM_05601, 75%). A previous study in Aspergillus fumigatus indicated that an oxidosqualene cyclase (Afu4g14770) is required for helvolic acid biosynthesis (Mitsuguchi et al, 2009). Likewise, the homolog of this cyclase is present in M. robertsii (MAA_06578, 63%), M. acridum (MAC_09947, 38%), and M. album (MAM_07210, 39%).…”
Section: Discussionmentioning
confidence: 99%
“…10). The corresponding triterpene synthase and associated fusidane biosynthetic gene cluster has been identified by two groups [222,223] (Fig. 10).…”
Section: Fungal Triterpenoid Biosynthesismentioning
confidence: 99%
“…A putative oxidosqualene cyclase gene with some sequence identity to fungal lanosterol synthase genes was identified in the A. fumigatus genome, as well as tailoring genes and a transporter gene that all cluster together and could plausibly contribute to helvolic acid biosynthesis. 111 The OSC gene, AfuOSC3 , was PCR amplified and expressed in yeast, the transformant bearing a known precursor to helvolic acid. Coexpression with the cluster's dehydrogenase/reductase gene or a P450 gene yielded oxidized backbone products that are in agreement with the idea the cluster is responsible for forming a tetracyclic ring system which is then tailored to helvolic acid.…”
Section: Genetic Characterization Of Other Aspergillus Secondary Mementioning
confidence: 99%